? SYNTHESIS AND ELECTRONIC ABSORPTION SPECTRA OF SOME Azo DYES AND THEIR ANALOGUES AZOMETHINES (Biological Sciences - PJSIR, 1998)
UV- Visible Absorption Spectroscopic Properties. Ultraviolet-Visible absorption spectroscopic data for dyes 1,2 and3 are summarized in Table 2. Absorption maxima in varioussolvents are also given.